Strategic management competitiveness & globalization : concepts & cases - Hitt, Michael A.; Ireland, R. Duane; Hoskisson, Robert E. (Cengage Learning Asia Pte Ltd, 2020)
Introduce students to strategic management with the market-leading text that sets the standard for this course. Strategic management : competitiveness & globalization, 13e provides an intellectually rich, yet practical, analysis of strategic management. The authors combine a classic industrial organization model with a resource-based view of the firm to clearly demonstrate how today's businesses establish competitive advantages and create value for stakeholders. Also included at no additional charge are 20 leading business cases, carefully selected by the authors, which cover several US and international businesses across many industries. Cutting-edge research provides a strong global focus and helps students more accurately interpret the actions of more than 600 emerging and established companies that are striving to serve stakeholders and gain a competitive advantage over their rivals. Almost all opening cases are new to this edition as they introduce chapter concepts to readers. Updates to this edition's other cases provide fresh insights and reflect the latest developments. All-new mini cases in each chapter offer new contexts of study. In addition, MindTap online learning solution offers resources to help prepare your students to excel as strategic leaders, including you make the decision exercises, what would you do video activities and adaptive test prep.